2015
DOI: 10.2118/164477-pa
|View full text |Cite
|
Sign up to set email alerts
|

Pipe-Diameter Effect on Liquid Loading in Vertical Gas Wells

Abstract: Summary The effect of pipe diameter on liquid-loading initiation has been investigated experimentally with pipes having internal diameters of 5.1- (2-) and 10.2-cm (4-in.). Two-phase-flow parameters, such as pressure gradient and liquid holdup, were measured. Flow characteristics were determined by visual observation with a high-speed video camera. Critical gas-flow rate for liquid-loading initiation was identified, and comparisons between the two pipe diameters were presented. The critical supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…It exhibits an inverse relationship and an ability to adjust to the liquid velocity, system pressure, and pipe diameter. The previous data [18], [35], [36] show good agreement at low superficial liquid velocities of between 0.01-0.05 m/s, while the current data, which gave higher film thicknesses due to the larger liquid flow rates, showed that the correlation also gives excellent predictions at higher liquid flow.…”
Section: Figure 12: Bar Charts Showing Comparison Between the Non-dimsupporting
confidence: 75%
See 1 more Smart Citation
“…It exhibits an inverse relationship and an ability to adjust to the liquid velocity, system pressure, and pipe diameter. The previous data [18], [35], [36] show good agreement at low superficial liquid velocities of between 0.01-0.05 m/s, while the current data, which gave higher film thicknesses due to the larger liquid flow rates, showed that the correlation also gives excellent predictions at higher liquid flow.…”
Section: Figure 12: Bar Charts Showing Comparison Between the Non-dimsupporting
confidence: 75%
“…A wide range of flow regimes was covered in the experiments, and for the comparisons, careful screening was done to select only those that fall in the annular regime ( Figure 10). Previous measurements of a liquid holdup in a 101.6-mm riser were also used to study liquid loading phenomena [35]. Those experiments were carried out around atmospheric pressure, and 9 data points…”
Section: Description Of Large Pipe Experimental Datasetsmentioning
confidence: 99%
“…Since many of the studies have not been focused on down-and up-ward flow, the primary purpose of it, is to propose the CFD as a reliable alternative for the prediction of flow patterns and operational parameters such as void fraction in comparison to empirical correlations or other commercial computational codes. For this, it is used to replicate and validate the CFD model against 36 different experimental conditions from Chung [2] and Skopich [23]. Then, a comparison of the obtained results against two other methods like OLGA and 66 empirical correlations for the void fraction prediction will be made.…”
Section: State Of the Artmentioning
confidence: 99%
“…Two different experimental facilities were used, both located at University of Tulsa (Tulsa, OK, US) and described in detail by Chung [2] and Skopich [23], this section makes a brief description of these facilities.…”
Section: Experimental Facilities For the Oil-gas Flow Measurementsmentioning
confidence: 99%
See 1 more Smart Citation